Detection of Potential Natural Disasters Due to the Rate of Land Change in Sinjai Indonesia Regency with Geospatial Technology - Muhlis ,Fatmawati, Iradhatullah Rahim, Syamsia (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Sinjai, Indonesia Regency is an area that is often hit by floods and landslides, drought, forest fires with the following data: potential natural disasters that often occur in Sinjai Regency are landslides and flash floods. This disaster is the impact of land use change. Landslides and flash floods often occur at the same time, especially if there is heavy rain. The objectives of this study are (1) to evaluate the rate of change in temporal land cover between 2014 and 2019 in Sinjai Regency. 2) To detect the impact of disasters caused by the conversion of land functions in Sinjai Regency. This research uses quantitative methods. This research is closely related to the enumerative induction process (calculation based induction). Based on the results of land cover classification using different image data in the year of updating, this data indicates strongly that in 2014 to 2019 there was a rate of land change which had a major influence on all watershed areas in Sinjai Regency, the impact of the rate of land change can increase the runoff thickness. The greatest rate of change is the change from primary forest to mixed agriculture and a shift in land use due to settlement, opening of new rice fields and other uses which constitute forest conversion. The survey activities conducted by the survey team indicated that mining activities (especially sand mining around the river) led to the opening of some areas that were previously dominated by forest to become type C mining activities, this type of activity is the main cause of runoff when it rains and has the potential erosion that can result in silting, such as that of the Saleo river, which is a tributary of the Garaccing watershed.